A Novel Donkey Milk–derived Human Milk Fortifier in Feeding Preterm Infants: A Randomized Controlled Trial. Issue 1 (January 2019) - Bertino, Enrico; Cavallarin, Laura; Cresi, Francesco; Tonetto, Paola; Peila, Chiara; Ansaldi, Giulia; Raia, Melissa; Varalda, Alessia; Giribaldi, Marzia; Conti, Amedeo; Antoniazzi, Sara; Moro, Guido E.; et al.
ABSTRACT: Objectives: The purpose of the present randomized controlled clinical trial was to compare the use of donkey milk–derived fortifier (DF) with commercial bovine milk–derived fortifier (BF) in very preterm or very-low-birth-weight newborns, in terms of feeding tolerance. Methods: This trial included 156 newborns born at <32 weeks of gestational age and/or with a birth weight ⩽1500 g. Newborns were randomized 1:1 to receive enteral feeding with either a BF-arm, or a new, DF-arm for 21 days. The fortification protocol was the same for both study arms, and the 2 diets were designed to be isoproteic and isocaloric. Feeding tolerance was assessed by a standardized protocol. Results: The risk of feeding intolerance tended to be lower in DF-arm than in BF-arm, with a relative risk reduction of 0.63 (95% confidence interval: −0.29, +0.90). The mean number of episodes per newborn of feeding intolerance and feeding interruptions (any duration) were consistently lower in the DF-arm than in the BF-arm. Episodes of bilious gastric residuals and vomiting were significantly lower in the DF-arm. Time needed to reach full enteral feeding (150 mL · kg −1  · day −1 ) and daily weight increase between the first day of exclusive enteral feeding (ie, without administering intravenous fluids) and discharge were similar in the BF- and DF-arms. Conclusions: These results suggest that DF improve feeding tolerance when compared with standard bovine-derived fortifiers, with a similar auxological outcome. Abstract : Supplemental Digital Content is available in the text